A Rare Brain Tumour-Gliosarcoma (Medicine Today, 2017)
A 57-year-old gentleman presented with a history of leftsided weakness and loss of appetite. Brain MRI was suggestive of right frontal and thalamic mass lesion with contrast enhancement at the periphery. Open biopsy examination revealed a malignant brain tumour presenting a biphasic tissue pattern with gliomatous and mesenchymal components suggestive of gliosarcoma. Although the treatment of gliosarcomas is almost similar to glioblastomas (surgical resection and depending on clinical status, radiotherapy and/or chemotherapy) the prognosis of gliosarcomas remains poor.Medicine Today 2016 Vol.28(1): 46-47